Analisis Penjatuhan Pidana kepada Pelaku Tindak Pidana Asal Usul Perkawinan dan Penelantaran dalam Rumah Tangga (Studi Putusan Nomor: 287/Pid.B/2023/PN.Mgl) - Vienna Egitha Qurratu Aini; Erna Dewi; Rini Fathonah (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
Criminal acts may occur concurrently (concursus), as seen in cases combining the falsification of marital status and domestic neglect. This study examines the judicial considerations in sentencing perpetrators of concursus delicti between the crime of falsifying marital status and domestic neglect, as reflected in Decision No. 287/Pid.B/2023/PN.Mgl, and evaluates whether the imposed sentence fulfills the principle of justice. This research employs a normative legal method using statute and conceptual approaches, with data collected through literature studies comprising primary, secondary, and tertiary legal materials. The analysis was conducted qualitatively to interpret legal norms and judicial reasoning. The findings reveal that the judges based their decisions on juridical, philosophical, and sociological considerations, reflecting efforts to achieve fairness for both the perpetrator and the victim. The three-year imprisonment sentence was deemed proportionate, balancing deterrence and rehabilitation. However, justice for the victim remains incomplete due to the absence of explicit legal provisions on compensation for victims of domestic neglect. The study concludes that future sentencing should not only ensure legal certainty but also emphasize restorative and victim-oriented justice within Indonesia’s criminal justice system.